Diseño De Instrumento Para Evaluar Clima Organizacional De Universidades Públicas En México - Hortensia Hernández Vela; Norma Patricia Garrido; Ma. Concepción Rico Pérez (European Scientific Journal, ESJ, 2016)
The measuring of organizational climate aims to obtain feedback that can inform an organization on ways in which to make improvements; not only in the work environment, but also in the quality of it; hence, it is important to possess instruments that provide reliable information of what is intended to be measured. Describing the building process of an organizational climate instrument is the objective of the present article, in which, after having established the relevance of the topic in the introduction; the stages developed for the elaboration and validation of the measuring instrument of the organizational climate perceived by professors of Higher Education Institution are presented. The result of this process is an instrument with four factors and nineteen dimensions.